Evolution of Resistant Mutants in Pseudomonas aeruginosa Persister Cells Under Meropenem Treatment - Jie Feng; Yifan Bian; Congjuan Xu; Zhihui Cheng; Yongxin Jin; Shouguang Jin; Weihui Wu (Microorganisms)
Bacterial persisters are dormant cells that survive antibiotic treatment, serving as a reservoir for the emergence of resistant mutations. The evolution of antibiotic resistance poses a significant challenge to public health. In this study, we investigated the development of resistance in Pseudomonas aeruginosa persister cells by exposing the reference strain PA14 to meropenem and tracked the emergence of resistance mutations over serial passages. Whole-genome sequencing of the populations or individual resistant strains revealed evolutionary trajectories. In the initial passages, low-level meropenem-resistant mutants harbored various mutations, accompanied by increasing population survival. Then, mutations in the oprD gene appeared, followed by mutation in the mexR gene in most of the cells, leading to high-level meropenem resistance and collateral resistance to ciprofloxacin. Our study provides insights into the evolutionary pathways of P. aeruginosa under lethal antibiotic pressure, highlighting the dynamic interplay between persister cells and the emergence of resistance mutations.